INITIAL STUDY ON FISH FAUNA IN THE THU BON ESTUARY OF QUANG NAM PROVINCE - Vi, Nguyen Thi Tuong; Thao, Le Thi Thu; No, Bui Thi Ngoc; Quang, Vo Van (Vietnam Journal of Marine Science and Technology, 2015)
This report presents the result of four surveys in 2013 at 12 sampling stations on fish composition of fish fauna in the Thu Bon estuary of Quang Nam province (the central Vietnam) and a total of 139 species of fishes were identified belonging to 110 genera, 63 families and 17 orders. Analysis of community structure of fish fauna showed that the order Perciformes was the most popular, making up 56.1%; Cypriniformes (8.6%); Pleuronectiformes (6.5%); Clupeiformes and Siluriformes (4.3%); Anguilliformes, Tetraodontiformes (3.6%); Mugiliformes (2.9%); ... The family Gobiidae was the most abundant with 12 species, making up 8.6% of the total number of species; Cyprinidae (10 species, 7.2%); Leiognathidae, Carangidae had the same number of species (6 species, 4.3%); Clupeidae, Lutjanidae: 5 species (3.6%); Serranidae, Mugilidae, Soleidae, Gerreidae, Ambassidae, Tetraodontidae: 4 species (2.9%); In addition, 4 families had 3 species, 12 families had 2 species and 35 families had 1 species. Cluster analysis based on the Bray - Curtis similarity index of nine fish faunas (Bach Dang, Thai Binh, Bu Lu, Son Tra peninsula, Thu Bon, coastal wetlands of Quang Nam, Nha Phu - Binh Cang, Ben Tre and Tra Vinh) showed that fish composition of the coastal - estuaries of Tra Vinh and Ben Tre had the highest similarity (78%), subsequently fish faunas of Thu Bon had similarity with that of Quang Nam (47%), Quang Nam and Nha Phu - Binh Cang (41%), Bu Lu and Thu Bon (38%). The result was also classified into three distinct groups of 9 fish faunas: group 1- Tra Vinh, Ben Tre and Thai Binh; group 2- Quang Nam, Thu Bon, Nha Phu - Binh Cang, Son Tra and Bu Lu; group 3- Bach Đang. The species richness (Margalef’s index) of Thu Bon (28.0) was less abundant than that of other areas: the highest species richness belonging to Tra Vinh (39.4), Thai Binh (38.6), Nha Phu - Binh Cang (35.9), Son Tra (31.8), Bu Lu (29.7), … The diversity of species composition according to the taxa in each region showed the characteristic of each fish fauna. The fish fauna is evidently typical of characteristics of the estuarine waters and coastal lagoons. There are 4 threatened species which are listed in the Vietnam’s Red Data Book (2007) at ex-tremely vulnerable levels.